2023
DOI: 10.1051/0004-6361/202245598
|View full text |Cite
|
Sign up to set email alerts
|

Long-term optical variability of the Be/X-ray binary GRO J2058+42

Abstract: Context. GRO J2058+42 is a transient hard X-ray pulsar that occasionally goes into outburst. The optical counterpart is a poorly studied OB-type companion. Aims. We investigate the long-term optical variability of the Be/X-ray binary GRO J2058+42 and the possible connection with periods of enhanced X-ray activity. Methods. We performed an optical spectroscopic and photometric analysis on data collected during about 18 yr. We also present the first optical polarimetric observations of this source. Results. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Optical observations of this companion star obtained in 2021 classified it as spectral type B1-3e III-V, indicating that MAXI J0655−013 is an example of a Be X-ray Binary (BeXRB; Zaznobin et al 2022). Further optical observations in September 2022 suggested that the companion has spectral type O9.5-B0V, confirming the classification of MAXI J0655−013 as a BeXRB (Reig et al 2022).…”
Section: Introductionsupporting
confidence: 63%
“…Optical observations of this companion star obtained in 2021 classified it as spectral type B1-3e III-V, indicating that MAXI J0655−013 is an example of a Be X-ray Binary (BeXRB; Zaznobin et al 2022). Further optical observations in September 2022 suggested that the companion has spectral type O9.5-B0V, confirming the classification of MAXI J0655−013 as a BeXRB (Reig et al 2022).…”
Section: Introductionsupporting
confidence: 63%
“…The long-term variability of CPD −29 2176 is best explored with the time series from ground-based surveys such as ASAS, shown in Figure 4. The photometric data do not show evidence of eclipses but do show long-term variations similar to other Be stars (Labadie- Bartz et al 2017;Bernhard et al 2018), including Be XRBs (Reig & Fabregat 2015;Reig et al 2023). In the ASAS data, we see multiple peaks in the light curve with a timescale of ∼600 days.…”
Section: Photometric Variabilitymentioning
confidence: 57%
“…Some of these mechanisms involve variations in the companion star and/or the circumstellar disk of the Be star and can produce optical variability of tenths of magnitudes. They comprise different scenarios such as ejections of matter from the Be star (Hubert & Floquet 1998;Mennickent et al 2002), precession, and/or warping or changes in the inclination of the circumstellar disk (Okazaki et al 2013;Martin et al 2014;Martin & Franchini 2019), as well as the formation and dissipation of the circumstellar disk (see for example Reig et al 2023).…”
Section: Introductionmentioning
confidence: 99%